2022
DOI: 10.1111/mec.16781
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐genome resequencing reveals complex effects of geographical–palaeoclimatic interactions on diversification of moustache toads in East Asia

Abstract: Geographical features and palaeoclimatic fluctuations are two classical evolutionary forces that shape genetic diversification within species. Fine-grained analysis of the mechanisms involved through population demographic processes, however, remains limited. Taking advantage of two recently published reference genomes, we

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 109 publications
(142 reference statements)
0
6
0
Order By: Relevance
“…The results of the AMOVA also indicated that genetic variation primarily occurs within populations of R. hanluica However, higher genetic differentiation (0.0856–0.7429) reflected the existence of differentiation between populations of R. hanluica, possibly due to genetic drift (Zhang et al, 2018). Previous studies have shown that the causes of genetic differentiation in amphibians in southern China are mainly geological history ( Tian et al, 2018 ; Li et al, 2022 ), climate fluctuations ( Li et al, 2018 ), and sky islands ( Shepard and Burbrink, 2009 ; Pan et al, 2019 ). The distribution range of R. hanluica is in the middle and low altitudes, and its breeding environment is limited by stagnant waters such as ponds and paddy fields.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the AMOVA also indicated that genetic variation primarily occurs within populations of R. hanluica However, higher genetic differentiation (0.0856–0.7429) reflected the existence of differentiation between populations of R. hanluica, possibly due to genetic drift (Zhang et al, 2018). Previous studies have shown that the causes of genetic differentiation in amphibians in southern China are mainly geological history ( Tian et al, 2018 ; Li et al, 2022 ), climate fluctuations ( Li et al, 2018 ), and sky islands ( Shepard and Burbrink, 2009 ; Pan et al, 2019 ). The distribution range of R. hanluica is in the middle and low altitudes, and its breeding environment is limited by stagnant waters such as ponds and paddy fields.…”
Section: Discussionmentioning
confidence: 99%
“…Third, demographic parameters with limited resolution, which is often a consequence of limited amount of data and analysis, likely contribute to questionable conclusion. For example, Bayesian skyline plots based on 1622 bp of mitochondrial sequences of two moustache toads ( Leptobrachium boringii and L. liui ) showed that most populations had stable N e over time during the LGM (Li et al, 2018); however, recent study based on whole genome data clearly showed that they likely experienced periodic changes and a clear decline at the LGM (Li et al, 2022). Fourth, a general lack of fossil data for most animal species may limit inference.…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%
“…These data and analytic tools allow fine-scale analysis, including inference of population level processes, demographic parameters and deep history beyond Pleistocene, which have potentials to link historical microevolutionary processes to macroevolutionary patterns. Recent studies on the giant panda (Zhao, Zheng, et al, 2013), the Himalayan frog (Wang et al, 2018), the Chinese pangolin (Wei et al, 2022) and the moustache toads (Li et al, 2022) have demonstrated the power of the new approaches. Additionally, ancient DNA started to play an important role.…”
Section: Per S Pec Tive S and Future Direc Tionsmentioning
confidence: 99%
“…Complex geological events can result in physical barriers, such as mountains, rivers, and marine incursions, which can prevent gene flow between closely related species or populations. Furthermore, unfavorable climate changes should cause populations to contract, on the contrary, a favorable climate may lead to population expansion (Berv et al., 2021; Fijarczyk et al., 2011; Li et al., 2022; Myers et al., 2019, 2020; Pyron & Burbrink, 2009; Ursenbacher et al., 2008; Yang et al., 2022; Zhao et al., 2022). However, the influence of both factors on these processes differ in the timing and effect among different regions (such as Asia and North America) and among groups (such as birds and reptiles).…”
Section: Introductionmentioning
confidence: 99%